Sex-related difference in susceptibility to cypress mortality in Austrocedrus chilensis from Northwestern Patagonia (Argentina) = Susceptibilidad diferencial al mal del ciprés entre sexos de Austrocedrus chilensis en la Patagonia (Argentina) - El Mujtar, Veronica Andrea; Pareja Perdomo, Mariano; Gallo, Leonardo Ariel; Grau, Oscar (Facultad de Ciencias Forestales y Recursos Naturales, Universidad Austral de Chile, 2019)
Female and male individuals of dioecious species have different reproductive functions and sex-related differences have been reported in growth rate, age at maturity, size, spatial distribution and physiological responses to biotic and abiotic stress. Austrocedrus chilensis (ciprés de la cordillera) is a dioecious conifer native to Patagonian Temperate Forests. Austrocedrus chilensis forests in Argentina are seriously affected by cypress mortality which has been related to drought events and biotic agents. Sex-related differences in age at maturity, reproductive cost and their mitigation, that could influence the responses to cypress mortality, have been reported for A. chilensis. However, until now no study has been conducted to evaluate sex-related differences in the susceptibility of A. chilensis trees to cypress mortality. In this work we detected a higher proportion of female individuals among trees affected by cypress mortality than that detected among symptomless trees. Our results suggest that cypress mortality could determine not only sex ratio bias but also changes in reproductive dynamics in A. chilensis forests.